Exploring Personal Relationships in Family Businesses - Jagannathan, Sahana (2020)
It is generally agreed that family and businesses are two complicated structures on their own. Combined, they are intricate in its functioning, and the relationship between these two provide a unique insight into the workings of a family business. The aim of this dissertation is to explore this connection, and understand the impact of personal relationships on family businesses. The study revolves around one family business located in Chennai, India, and the relationship between the four members of the family in a business environment. Research was conducted using a semi-structured, qualitative interview method, and the interview questions were structured according to the family member being studied. The research is. based around themes of succession, parental upbringing of the second generation, practising fairness in the workplace amongst family and nonfamily employees, and the impact of these factors on the firm performance. A grounded theory approach was used with the interpretivist method of analysis. There seem to be differences in the results obtained in this study and the literature reviewed, with culture and societal values being a factor that could have brought about these differences. Because of the complicated nature and unique characteristics of family businesses and diversity in India, results cannot be generalised.